(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the period of the reighn of Mallakhon in Kokand Khanate (1858-1862) on the basis of different historical manuscripts, scientific sources, scientific works and monographs. The political processes and the struggle for the government caused by different events are analyzed. The political relations between Bukhara and Kokand khanates of this period are also revealed in it.